Ischemic Core Overestimation on Computed Tomography Perfusion. Issue 5 (8th March 2021) - García-Tornel, Álvaro; Campos, Daniel; Rubiera, Marta; Boned, Sandra; Olivé-Gadea, Marta; Requena, Manuel; Ciolli, Ludovico; Muchada, Marian; Pagola, Jorge; Rodriguez-Luna, David; Deck, Matias; Juega, Jesus; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Different studies have pointed that CT perfusion (CTP) could overestimate ischemic core in early time window. We aim to evaluate the influence of time and collateral status on ischemic core overestimation. Methods: Retrospective single-center study including patients with anterior circulation large-vessel stroke that achieved reperfusion after endovascular treatment. Ischemic core and collateral status were automatically estimated on baseline CTP using commercially available software. CTP-derived core was considered as tissue with a relative reduction of cerebral blood flow <30%, as compared with contralateral hemisphere. Collateral status was assessed using the hypoperfusion intensity ratio (defined by the proportion of the time to maximum of tissue residue function >6 seconds with time to maximum of tissue residue function >10 seconds). Final infarct volume was measured on 24 to 48 hours noncontrast CT. Ischemic core overestimation was considered when CTP-derived core was larger than final infarct. Results: Four hundred and seven patients were included in the analysis. Median CTP-derived core and final infarct volume were 7 mL (interquartile range, 0–27) and 20 mL (interquartile range, 5–55), respectively. Median hypoperfusion intensity ratio was 0.46 (interquartile range, 0.23–0.59). Eighty-three patients (20%) presented ischemic core overestimation (median overestimation, 12 mL [interquartile range, 41–5]). Multivariable logistic regression analysis adjusted by CTP-derived core and confounding variables showed that poor collateral status (per 0.1 hypoperfusion intensity ratio increase; adjusted odds ratio, 1.41 [95% CI, 1.20–1.65]) and earlier onset to imaging time (per 60 minutes earlier; adjusted odds ratio, 1.14 [CI, 1.04–1.25]) were independently associated with core overestimation. No significant association was found with imaging to reperfusion time (per 30 minutes earlier; adjusted odds ratio, 1.17 [CI, 0.96–1.44]). Poor collateral status influence on core overestimation differed according to onset to imaging time, with a stronger size of effect on early imaging patients( P interaction <0.01). Conclusions: In patients with large-vessel stroke that achieve reperfusion after endovascular therapy, poor collateral status might induce higher rates of ischemic core overestimation on CTP, especially in patients in earlier window time. CTP reflects a hemodynamic state rather than tissue fate; collateral status and onset to imaging time are important factors to consider when estimating core on CTP.